Fake SAR Signal Generation Method Based on Noise Convolution Modulation - Datong HUANG; Shiqi XING; Yemin LIU; Yongzhen LI; Shunping XIAO (Leida xuebao, 2020)
Suppression position of the traditional noise convolution modulation Synthetic Aperture Radar (SAR) jamming lags behind in range and suppression area in azimuth is uncontrollable. Considering this defect, an enhanced jamming method is proposed herein. First, the frequency of the intercepted signal is shifted in fast-time to control the suppression position in range. Then, the convolution with the noise is implemented, which has been filtered in slow-time, to control the suppression area in azimuth. Theoretical analysis and simulation results demonstrate that the proposed jamming method can efficiently control the jamming position in range and suppression area when compared with the traditional noise convolution modulation jamming. Even if some reconnaissance errors exist, the local scenario can still be shielded effectively. Furthermore, the utilization efficiency of jamming energy is also improved under the same condition, which will provide some reference values and inputs for engineering applications.